2010
DOI: 10.1523/jneurosci.1428-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

The Representation of S-Cone Signals in Primary Visual Cortex

Abstract: Recent studies of middle-wavelength-sensitive and long-wavelength-sensitive cone responses in primate primary visual cortex (V1) have challenged the view that color and form are represented by distinct neuronal populations. Individual V1 neurons exhibit hallmarks of both color and form processing (cone opponency and orientation selectivity), and many display cone interactions that do not fit classic chromatic/achromatic classifications. Comparable analysis of short-wavelength-sensitive (S) cone responses has y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
29
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 85 publications
(135 reference statements)
6
29
0
Order By: Relevance
“…This hypothesis is further supported by fMRI studies that directly compared the activity in human LGN and V1 in response to cone-specific stimuli (Mullen et al, 2010; D’Souza et al, 2011). It is also consistent with imaging studies on marmosets (Buzas et al, 2008) and tree shrews (Johnson et al, 2010) that found widespread activation in V1 in response to S-cone stimulation. Finally, an EEG study on human V1 found strong S-cone inputs to the mechanism underlying surround suppression (Xiao & Wade, 2010), although this mechanism was found to receive predominantly achromatic inputs in a study of single neurons in monkey V1 (Solomon et al, 2004).…”
Section: Strength Of the S-cone Inputs To Cells In V1supporting
confidence: 89%
“…This hypothesis is further supported by fMRI studies that directly compared the activity in human LGN and V1 in response to cone-specific stimuli (Mullen et al, 2010; D’Souza et al, 2011). It is also consistent with imaging studies on marmosets (Buzas et al, 2008) and tree shrews (Johnson et al, 2010) that found widespread activation in V1 in response to S-cone stimulation. Finally, an EEG study on human V1 found strong S-cone inputs to the mechanism underlying surround suppression (Xiao & Wade, 2010), although this mechanism was found to receive predominantly achromatic inputs in a study of single neurons in monkey V1 (Solomon et al, 2004).…”
Section: Strength Of the S-cone Inputs To Cells In V1supporting
confidence: 89%
“…Ferret: (Baker, Thompson et al 1998). Tree shrew : (Johnson, Van Hooser et al 2010). Marmoset : (Forte, Hashemi-Nezhad et al 2005).…”
Section: Figurementioning
confidence: 99%
“…A growing body of evidence shows that many double-opponent neurons are orientation-selective for both color and achromatic patterns, regardless of the constitution of cone input (Thorell et al, 1984; Conway, 2001; Johnson et al, 2001; Conway et al, 2002; Heimel et al, 2005; Conway and Livingstone, 2006; Horwitz et al, 2007; Johnson et al, 2008; Johnson et al, 2010). This transformation means that these cells respond to cues for form, such as boundaries and edges, and may take signals from color or black and white as needed.…”
Section: Striate Cortex Mechanismsmentioning
confidence: 99%
“…The neural basis of color has been reviewed previously from a range of perspectives (Gegenfurtner, 2003; Gegenfurtner and Kiper, 2003; Lennie and Movshon, 2005; Sincich and Horton, 2005; Solomon and Lennie, 2007; Conway, 2009; Dobkins, 2009; Jacobs and Nathans, 2009; Stockman and Brainard, 2010). Here we focus on advances and pressing questions regarding the mechanisms of color in retina, striate cortex and extrastriate cortex of non-human primates, although we note that other species are emerging as excellent model systems of color processing (Lotto and Chittka, 2005; Van Hooser and Nelson, 2006; Osorio and Vorobyev, 2008; Borst, 2009; Johnson et al, 2010; Srinivasan, 2010). …”
mentioning
confidence: 99%